Is Sexual Attraction Independent of the Instrumental and Expressive Traits? - Quiroga, María Ángeles; Olmo, Isabel del; Fernández, Juan (The Spanish Journal of Psychology, 2006)
Sexual attraction is an essential part of sex, just as the instrumental and expressive traits are the mainstay of gender. Various hypotheses concerning the dimensionality and independence versus dependence/overlapping of these core entities were tested. A group of 423 university students completed the Sexual Attraction Questionnaire (SAQ; Fernández, Quiroga, & Rodríguez, 2006) and the 12-item Bem Sex Role Inventory (BSRI; Bem, 1974). Internal consistency and factor analyses (PAF) were conducted. The results support the dimensionality established for the SAQ and reveal some psychometric and conceptual weaknesses of the 12-item BSRI. The results also support the independence of the two cores: sexual attraction and the instrumental and expressive traits. The logical implications for the different viewpoints of the relations between sex and gender are discussed.